2017
DOI: 10.1519/jsc.0000000000001553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Energy Drinks on Economy and Cardiovascular Measures

Abstract: Peveler, WW, Sanders, GJ, Marczinski, CA, and Holmer, B. Effects of energy drinks on economy and cardiovascular measures. J Strength Cond Res 31(4): 882–887, 2017—The use of energy drinks among athletes has risen greatly. Caffeine and taurine are the 2 primary performance enhancing ingredients found in energy drinks. The number of emergency department visits involving energy drinks doubled over the past 5 years. Reviews of the health complications have highlighted adverse cardiovascular events. The literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…This is consistent with previous findings that caffeine doses in excess of 200 mg are generally required to produce clinically meaningful changes in cardiovascular parameters . However, some studies have reported significant effects on heart rate or blood pressure at doses as low as 80 mg . This may be due to other ingredients contained in the tested dosage forms such as glucose and taurine both common ingredient in energy drinks.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous findings that caffeine doses in excess of 200 mg are generally required to produce clinically meaningful changes in cardiovascular parameters . However, some studies have reported significant effects on heart rate or blood pressure at doses as low as 80 mg . This may be due to other ingredients contained in the tested dosage forms such as glucose and taurine both common ingredient in energy drinks.…”
Section: Discussionsupporting
confidence: 91%
“…There are numerous studies which investigated the acute effects of caffeinated beverages on haemodynamic parameters, such as blood pressure and heart rate variability. 1,[4][5][6] For instance, Hajsadeghi et al 7 reported a significant heart rate decline and Peveler et al 8 showed a significant increase in systolic blood pressure after the consumption of energy drink. Consequently, a number of studies have shown the adverse effects of caffeinated beverages on cardiovascular system, but the dynamics and the mechanism are still ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects ingested one of three energy drinks or a placebo one hour prior to testing. Results showed that the fifteen minute systolic BP readings were significantly higher in the three energy drink trials (163.87, 166.47, and 165.00) compared to the placebo trials (156)[ 12 ]. Other studies have found the same effect as well.…”
Section: Purported Effects Of Energy Drinks and Their Caffeine-relatementioning
confidence: 99%